Isolation of a Perfectly Linear Uranium(II) Metallocene - Guo, Fu‐Sheng; Tsoureas, Nikolaos; Huang, Guo‐Zhang; Tong, Ming‐Liang; Mansikkamäki, Akseli; Layfield, Richard A. (Angewandte Chemie, 2020)
Reduction of the uranium(III) metallocene [(η 5 ‐C 5 i Pr 5 ) 2 UI] ( 1 ) with potassium graphite produces the “second‐generation” uranocene [(η 5 ‐C 5 i Pr 5 ) 2 U] ( 2 ), which contains uranium in the formal divalent oxidation state. The geometry of 2 is that of a perfectly linear bis(cyclopentadienyl) sandwich complex, with the ground‐state valence electron configuration of uranium(II) revealed by electronic spectroscopy and density functional theory to be 5f 3 6d 1 . Appreciable covalent contributions to the metal‐ligand bonds were determined from a computational study of 2 , including participation from the uranium 5f and 6d orbitals. Whereas three unpaired electrons in 2 occupy orbitals with essentially pure 5f character, the fourth electron resides in an orbital defined by strong 7s‐6d mixing.